Sudden Cardiac and Noncardiac Death in Sports: Epidemiology, Causes, Pathogenesis, and Prevention - Lippi, Giuseppe; Favaloro, Emmanuel J.; Sanchis-Gomar, Fabian (Seminars in Thrombosis and Hemostasis, 2018)
Although few doubts remain that physical exercise should be widely promoted for maintenance of health and fitness, the risk of adverse events such as sudden death (especially due to cardiac causes, i.e., sudden cardiac death [SCD]) during exercise remains tangible. The overall risk of sudden death in athletes is relatively low (i.e., usually comprised between 0.1 and 38/100,000 person-years), and globally comparable to that of the general population. However, up to 20% of all sudden death cases are still recorded while exercising. The most frequent underlying disorders encountered in SCD are hypertrophic cardiomyopathy and coronary artery disease (CAD), representing three quarters of all conditions. The risk related to CAD increases with aging (>35 years old), while that attributable to cardiomyopathies or fatal arrhythmias is especially frequent among young people (<35 years old). Taken together, these findings would lead to the conclusion that physical exercise may be seen as an acute trigger of myocardial ischemia or arrhythmias in some predisposed individuals. Nonetheless, the prevalence of coronary atherosclerosis seems to be higher in athletes than in sedentary subjects with comparable risk profile. On the contrary, coronary plaques in physically active subjects appear more stable, thereby attenuating the risk of rupture and subsequent myocardial ischemia. These findings, along with evidence of a considerable increase of peak coronary blood flow during exercise, make it very likely that an imbalance between oxygen demand and supply may be the most frequent cause of myocardial ischemia in athletes suffering SCD and/or cardiac arrest. Therefore, all subjects who wish to practice moderate- to high-intensity exercise are recommended to undergo preparticipation screening and annual follow-up.
Keywords: sudden death; cardiac arrest; sports; physical exercise; physical activity